Strain induced lifting of the charged exciton degeneracy in monolayer MoS2 on a GaAs nanomembrane. (1st October 2022) - Jasiński, Jakub; Balgarkashi, Akshay; Piazza, Valerio; Dede, Didem; Surrente, Alessandro; Baranowski, Michał; Maude, Duncan K; Banerjee, Mitali; Frisenda, Riccardo; Castellanos-Gomez, Andres; Fontcuberta i Morral, Anna; Plochocka, Paulina
Abstract: Strain is a commonly used tool to tune the optoelectronic properties of semiconductors. It is especially effective for transition metal dichalcogenides (TMDs), which can withstand extreme strain up to 10%. To date, localised strain fields have been applied by transferring TMDs flakes onto a patterned SiO2 substrate. Here, we present a novel approach, where the strain in MoS2 monolayer is induced by an array of homoepitaxially grown GaAs nanomembranes. This represents a first step towards the integration of TMD monolayers with III–V semiconductor nanostructures, which is essential to develop scalable nanophotonic platforms. The strain imposed by the nanomembrane lifts the degeneracy of the exciton states, leading to linearly polarised emission. The principal axis of the linear polarisation of the emission is strictly determined by the orientation of the nanomembranes. This result is fully consistent with the expected broken crystal symmetry resulting from the imposed uniaxial strain.